Art brut in America the incursion of Jean Dubuffet - Rousseau, Valérie; Lombardi, Sarah 1972- (American Folk Art Museum, 2015)
Published on the occasion of the exhibition "Art Brut in America: The Incursion of Jean Dubuffet," presented October 13, 2015-January 10, 2016, at the American Folk Art Museum, New York, and curated by Valérie Rousseau, Curator, Self-Taught Art and Art Brut -- title page